2007
DOI: 10.12968/bjon.2007.16.14.24325
|View full text |Cite
|
Sign up to set email alerts
|

Problems experienced by haemodialysis patients in Greece

Abstract: Even though Greece has a disproportionate number of haemodialysis stations for the treatment of end-stage renal disease (ESRD), and a rapidly rising number of patients on dialysis, there has been no study of the lived experience of haemodialysis treatment in Greece. ESRD and dialysis drastically impact patients' everyday life, therefore expectations and desires play a major role in adapting to alterations and restrictions. An understanding of these culturally-influenced expectations and desires is essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 15 publications
4
60
0
1
Order By: Relevance
“…It has been also reported that the world of a dialysis patient can be isolated and social activities are greatly reduced (Faber et al, 2003). Furthermore, several studies have shown that, in comparison to the general population, patients with ESRD commonly report reduced physical functioning and overall physical activities (Covic et al, 2004;Molsted et al, 2004;Kaba et al, 2007;Seica et al, 2009;Kring and Crane, 2009;Santos et al, 2009). The World Health…”
Section: Impact Of End-stage Renal Diseasementioning
confidence: 99%
“…It has been also reported that the world of a dialysis patient can be isolated and social activities are greatly reduced (Faber et al, 2003). Furthermore, several studies have shown that, in comparison to the general population, patients with ESRD commonly report reduced physical functioning and overall physical activities (Covic et al, 2004;Molsted et al, 2004;Kaba et al, 2007;Seica et al, 2009;Kring and Crane, 2009;Santos et al, 2009). The World Health…”
Section: Impact Of End-stage Renal Diseasementioning
confidence: 99%
“…When commencing hemodialysis, some participants struggled with feelings of vulnerability and their dependency on both dialysis treatment and caregivers (24,26,(28)(29)(30)(31)(32)(35)(36)(37)(38)(39)(40). The "assembly line" (26) nature of dialysis and lack of interest shown by staff could result in a loss of personal identity (24,26,28,35). Interference with earlier roles in society and social networks could also affect identity.…”
Section: Synthesismentioning
confidence: 99%
“…Interference with earlier roles in society and social networks could also affect identity. Those required to give up employment reported this affected their sense of self as reliable and able to provide for their families (29,35,40). Additionally, dialysis affected the physical self through the creation of vascular access and other changes in appearance (25,29,36,37,39).…”
Section: Synthesismentioning
confidence: 99%
“…Hemodialysis causes changes in individuals' lifestyle, health status and roles. These patients face with multiple physical, mental and social stressors (3). Patients treated with hemodialysis experience restrictions on lifestyle, diet and fluids (4).…”
Section: Introductionmentioning
confidence: 99%